ANALYSIS OF RECRUITMENT, SELECTION AND COMMUNICATION ON THE PERFORMANCE OF THE CREW AT PT. KAMANDANU JAYA SAMUDERA JAKARTA - Imam Suryono; Shinta Melati Sudarsono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of recruitment, selection, and communication on the performance of ship crews at PT. Kamandanu Jaya Samudera Jakarta. As an essential part of the national maritime industry, shipping operations require professional human resource management, particularly in the recruitment and selection processes of ship crews and communication between crewing staff and clients. The company faces several issues, including mismatches between crew competencies and client requirements, delays in crew placement, and communication problems that affect crew performance. This research employs a quantitative approach with a descriptive method. The population consists of 150 ship crews working at PT. Kamandanu Jaya Samudera, with a sample of 109 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires that had been tested for validity and reliability and analyzed using multiple linear regression analysis with SPSS software. The results indicate that recruitment, selection, and communication individually have a positive and significant effect on ship crew performance. Simultaneously, these three independent variables also significantly influence ship crew performance. These findings confirm that structured recruitment and selection processes, supported by effective communication between crewing staff and clients, can enhance ship crew performance. This study is expected to contribute both theoretically and practically to the development of human resource management strategies in the maritime and shipping industry.